OVERCOMING CHALLENGES OF ONLINE LEARNING: A STUDY ON UNDERGRADUATES' PREPAREDNESS DURING THE COVID-19 PANDEMIC - harianingsih, ika; Jusoh, Zailani (Jurnal Tatsqif, 2023)
The COVID-19 pandemic has forced educational institutions to transition to online learning to maintain social distancing. However, concerns have been raised that not all students may be equally prepared or equipped to succeed in this new environment. Therefore, it is essential to comprehend students' readiness for online learning during the pandemic and the challenges and barriers they may encounter to ensure inclusive and accessible education. This study aims to assess the preparedness of University Muhammadiyah Malang undergraduates in Indonesia for online learning during the pandemic. Using an online questionnaire, a quantitative survey approach was used to collect data from a sample of 260 undergraduates who enrolled in Foreign Language for Specific Purposes. The collected data was analyzed using descriptive statistics. Based on the data collected and analyzed, the study found that the students were not fully prepared for online learning during the COVID-19 pandemic. Although the undergraduates were motivated to learn through online learning and felt confident in basic computer and internet functions, they faced challenges in making personalized and successful decisions about their online educational activities during the pandemic. The study also revealed that factors such as access to technology and internet connectivity influenced their preparedness for online learning. These findings highlight the need for targeted support to enhance students' preparedness for online learning and improve their overall learning outcomes.